DILEMATIKA PEMEKARAN DAERAH DI INDONESIA - Anwaruddin, Awang (Pusjar SKPP Lembaga Administrasi Negara, 2007)
One the biggest issues recently protruding within the local autonomy framework is the goverment intention to postpone the widespread of regions.